Rett‐like phenotypes: expanding the genetic heterogeneity to the KCNA2 gene and first familial case of CDKL5‐related disease. Issue 3 (11th May 2016) - Allou, L.; Julia, S.; Amsallem, D.; El Chehadeh, S.; Lambert, L.; Thevenon, J.; Duffourd, Y.; Saunier, A.; Bouquet, P.; Pere, S.; Moustaïne, A.; Ruaud, L.; et al.
Abstract : Abstract : Several genes have been implicated in Rett syndrome (RTT) in its typical and variant forms. We applied next‐generation sequencing (NGS) to evaluate for mutations in known or new candidate genes in patients with variant forms of Rett or Rett‐like phenotypes of unknown molecular aetiology. In the first step, we used NGS with a custom panel including MECP2, CDKL5, FOXG1, MEF2C and IQSEC2 . In addition to a FOXG1 mutation in a patient with all core features of the congenital variant of RTT, we identified a missense (p.Ser240Thr) in CDKL5 in a patient who appeared to be seizure free. This missense was maternally inherited with opposite allele expression ratios in the proband and her mother. In the asymptomatic mother, the mutated copy of the CDKL5 gene was inactivated in 90% of blood cells. We also identified a premature stop codon (p.Arg926*) in IQSEC2 in a patient with a Rett‐like phenotype. Finally, exome sequencing enabled us to characterize a heterozygous de novo missense (p.Val408Ala) in KCNA2 encoding the potassium channel Kv 1.2 in a girl with infantile‐onset seizures variant of RTT. Our study expands the genetic heterogeneity of RTT and RTT‐like phenotypes. Moreover, we report the first familial case of CDKL5 ‐related disease.